The Roles of Subjective Task Values, Private Tutoring, and Emotions in Predicting Primary School Students’ English Achievement - Mu-Hsuan Chou (SAGE Open)
Learners’ English proficiency can be shaped by social environments, motivational factors, and emotions. According to situated expectancy-value theory, students’ expectations of success and subjective task values (STVs) influence academic performance. Achievement emotions, which refer to emotions directly related to learning activities or outcomes, also play a crucial role. This study examines the roles of STVs, duration of private English tutoring, and achievement emotions in predicting English achievement among primary school students in Taiwan. Additionally, it explores the types of STVs and achievement emotions experienced by young learners in English class. A total of 367 Grade 6 students participated in a questionnaire survey. Hierarchical multiple regression analysis revealed that the duration of private tutoring was the strongest positive predictor of English achievement, followed by emotions such as hope, anxiety, and hopelessness. Attainment value had the least predictive power. The duration of private tutoring was also positively associated with hope and negatively related to anger, anxiety, and boredom. It is recommended that instructional materials encourage students to reflect on task importance to foster a personal sense of relevance. Additionally, success-oriented tasks and positive feedback can help reduce classroom hopelessness and anxiety while fostering hope.